2015
DOI: 10.1097/md.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of EGFR Mutations in Pneumonic-Type Non-Small Cell Lung Cancer

Abstract: To retrospectively identify computed tomography (CT) features that correlate with epidermal growth factor receptor (EGFR) mutation in surgically resected pneumonic-type lung cancer (P-LC).A total of 953 consecutive patients with surgically resected lung cancer in the First Affiliated Hospital of Guangzhou Medical University from August 2011 to August 2013 were studied. The CT manifestations were reevaluated independently by 2 radiologists. The presence of pneumonic-type consolidation with pathological confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Pneumonic-type lesions were previously known as consolidation-type lung cancer and were typically misdiagnosed as inflammatory pulmonary consolidation. A few studies demonstrated that patients with pneumonic-type lesions experience a significantly increased incidence of EGFR mutations, independent of sex, histologic type, and smoking history 16 . That research focused on patients before surgery, and our study focused on biopsy patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pneumonic-type lesions were previously known as consolidation-type lung cancer and were typically misdiagnosed as inflammatory pulmonary consolidation. A few studies demonstrated that patients with pneumonic-type lesions experience a significantly increased incidence of EGFR mutations, independent of sex, histologic type, and smoking history 16 . That research focused on patients before surgery, and our study focused on biopsy patients.…”
Section: Discussionmentioning
confidence: 99%
“…n Pneumonia-like consolidation = a homogenous or heterogeneous opacity lesion in the lung Unlike ggo, pneumonia-like consolidation effaces the blood vessel shadows, and occasionally an air bronchogram can be displayed without any bacterial or obstructive pneumonia 16 .…”
Section: Ct Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…The BAC lesions were larger than AAH, with high density, air bronchogram, burring and leaf edges, thus these two types of cancer can be differentiated by CT. Yang et al reported that out of 55 cases of BAC, 56% showed air bronchogram (15). If BAC is of peripheral type, pleural indentation may be visible (16). Solid GGO is generally shown in adenocarcinoma, which is usually larger than an AHH lesion.…”
Section: Occurrence ----------------------------------------------mentioning
confidence: 99%
“…In patients with this histopathological diagnosis , EGFR mutation analysis should be considered as mandatory. Indeed, EGFR mutations appear to be significantly high in this histological subtype (17).…”
Section: The Oncologist's Point Of Viewmentioning
confidence: 99%